LACK OF EFFECTIVE COMMUNICATION AMONG YOUNG PEOPLE AS A CAUSE OF DISAGREEMENT - Aymuratova Zliyxa Janabay qızı, (TADQIQOTLAR, 2026)
Abstract:  Effective  communication  is  a  fundamental  skill  necessary  for maintaining  healthy  interpersonal  relationships.  Among  young  people,  the  lack  of effective communication has increasingly become a significant cause of disagreements in schools, families, peer groups, and online spaces. This article explores how poor communication skills—such as inability to express emotions clearly, poor listening habits,  misuse  of  digital  communication,  and  lack  of  conflict-resolution  skills—contribute  to  misunderstandings  and  conflicts  among  young  people.  The  study highlights  the  role  of  emotional  development,  social  influences,  and  modern technology in shaping communication patterns. By examining the causes and effects of  ineffective  communication,  the  article  emphasizes  the  importance  of  teaching communication  skills  to  reduce  disagreements  and  promote  mutual  understanding among youth.